Detection of Aflatoxin Content in Candlenut (Aleurites moluccana) Simplicia at Karang Penang Market using PDA (Potato Dextrose Agar) Method - Indriyani, Nova; Rahman, Alief Putriana; Humaidi, Fauzan (Universitas Airlangga, 2024)
Candlenut (Aleurites moluccana) was a food ingredient widely used as a cooking spice. Candlenuts that were stored for too long rotted more easily and grew fungi, especially Aspergillus niger and Aspergillus flavus. These types of fungi could produce mycotoxin compounds which were dangerous when consumed by humans. The purpose of this study was to determine the presence of aflatoxin content in candlenut (Aleurites moluccana) in the Karang Penang Sampang market. This research used total sampling. Candlenuts chosen as samples were all the candlenuts sold unwrapped by sellers in the Karang Penang market. This method used PDA media with the Pour Plate technique and an incubation time of 7 days. The results of the study showed 8 samples of candlenut with positive packaging containing the fungus Aspergillus niger with blackish-brown colonies and 1 sample of candlenut without positive packaging containing the fungus Aspergillus flavus with round yellowish-green colonies. In this study, it was concluded that the candlenuts circulating in the Karang Penang Sampang Market were positive for Aspergillus niger and Aspergillus flavus. Keywords: Soft Capsule, Increase Effectiveness, α-tocopherol, Vitamin E, Antioxidant